Culture – Health relationships in a quilombola community in Northeastern Brazil: Perceptions of the duality of traditional medicine / conventional medicine - Nink, Mariana Sahade; Nunes, Érika dos Santos; Nink, Ricardo Augusto (Seven Editora, 2023)
The Quilombolas constitute ethnic-racial groups with African ancestry, with their own historical trajectory, and endowed with specific territorial relations. The Quilombolas have been neglected in public health policies, despite being among the vulnerable populations in Brazil. This study sought to understand the relationships between culture and health within the context of valuing Quilombola traditions as a tool for promoting health in a remaining Quilombola community in the state of Alagoas. Through conducting interviews and employing a thematic content analysis, it was found that the population of the Village of Cruz uses non-conventional methods for restoring health, especially the use of medicinal plants, but seeks to adopt conventional medicine when their economic conditions allow. The majority of Quilombolas consider that traditional wisdom regarding health  is not valorized by health professionals. This finding highlights the need for a rescue of the users' historicity by health services, with a focus on respecting and understanding Quilombola cultural traditions, as an important tool for better adherence of this population to treatments developed based on the conventional biomedical model. DOI:https://doi.org/10.56238/sevened2023.004-050